The Potential of Some Non-Conventional Vegetable Oils in Biodiesel Applications (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
This work studied the potentials of some non-conventional oils biodiesel as an alternative to biodiesel made from a conventional seed oil (palm kernel oil), and petroleum-based diesel. The fruits of three non-conventional oilseeds, namely:PerseaAmericana (Avocado pear), Irvingiagabonenses (Dica nut) and Darcryodesedulis (Native pear)were obtained from local markets in Ile-Ife, Osun State Nigeria while petroleum-based diesel (PBD) used for comparative study was obtained commercially.The outer fleshylayers of the fruitswere separated from the seeds while both were air-dried for some days and later milled. The oils extracted from the milled samples were esterified to produce biodiesel usingmethanol in the presence of NaOH as catalyst. The biodiesels were analyzed for their fuel properties using standard methods.Results showed that the biodiesel yield ofIrvingiagabonensisoil diesel (IGOD),Darcryodesedulisoil diesel (DEOD) and Persia americanaoil diesel (PAOD) were94%, 82% and 96% respectively. These values compared favourably with that of palm kernel oil diesel (PKOD) (91%) produced under same conditions, and with the literature standard yield of 96.5% set for biodiesel. The pour pointsof PKOD, PAOD and DEOD were3, -6 and 1oC,respectively, with PAOD pour point very close to that of PBD (â‰¥-10oC) obtained under similar experimental conditions. Except for IGOD, all the oils have pour points within the standard range of -15 to 16oC set for biodiesel suggesting the suitability of the oils for biodiesel applications.The iodine values of the biodiesel ranged between 9.64 and 16.52 meq/kg and agreed closely with 12-18 meq/kg reported in literature for PKOD. The biodiesel blend with PBD in the ratio 10:90, 20:80, 30:70 and 40:60 demonstratedimprovedphysico-chemical properties (including smoke point, flash point, cloud point, pour point, density, viscosity and acid value) that could meet the fluidity requirements for biodiesel applications.